Genetic analysis along an invasion pathway reveals endemic cryptic taxa, but a single species with little population structure in the introduced range. Issue 1 (21st October 2015) - Hill, Matthew P.; Hoffmann, Ary A.; Umina, Paul A.; Cheng, Xuan; Miller, Adam D.
Abstract: Aim: The invasion pathways of pest arthropods can be traced using genetic tools to develop an understanding of the processes that have shaped successful invasions and to inform both pest management and conservation strategies in their non‐native and native ranges, respectively. The redlegged earth mite, Halotydeus destructor, is a major economic pest in Australia, successfully establishing and spreading after arrival from South Africa more than 100 years ago. Halotydeus destructor has recently expanded its range and evolved resistance to numerous pesticides in Australia, raising questions around its origin and spread. Location: South Africa and Australia. Methods: We sampled H. destructor populations in South Africa and Australia and developed a microsatellite marker library. We then examined genetic variation using mtDNA and microsatellite markers across both native and invasive ranges to determine endemic genetic diversity within South Africa, identify the likely origin of invasive populations and test genetic divergence across Australia. Results: The data show that H. destructor comprises a cryptic species complex in South Africa, with putative climatic/host plant associations that may correspond to regional variation. A lineage similar to that found near Cape Town has spread throughout Western and eastern Australia, where populations remain genetically similar. Main conclusions: Tracing the invasion pathway of this economically important pest revealed cryptic lineages in South Africa which points to the need for a taxonomic revision. The absence of significant genetic structure across the wide invasive range of H. destructor within Australia has implications for the development (and spread) of pesticide resistance and also points to recent local adaptation in physiological traits.